PENGARUH SERVANT LEADERSHIP DAN LINGKUNGAN KERJA MELALUI KOMITMEN ORGANISASI TERHADAP KINERJA GURU SMP NEGERI DI KABUPATEN TEMANGGUNG: - - Lestari, Peni; Fakhruddin; Tri Joko Raharjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of servant leadership and work environment on teacher performance, both directly and indirectly through organizational commitment as a mediating variable, among public junior high school teachers in Temanggung Regency. The research employed a quantitative approach using a survey method, involving 291 teachers from 11 public junior high schools selected through stratified random sampling. Data were analyzed using path analysis with IBM SPSS 25, and the Sobel test was conducted to examine the mediating variable. The results indicate that servant leadership and work environment have a significant positive effect on organizational commitment. Furthermore, servant leadership, work environment, and organizational commitment significantly and positively influence teacher performance. Indirectly, servant leadership and work environment also exert a significant positive effect on teacher performance through organizational commitment.